Electrocardiographic evaluation and serum cardiac troponin I levels in anemic dogs with blood parasitosis - Champion, Tatiana; Francoy, Cristiane [UNESP]; Pereira Neto, Glaucia Bueno; Camacho, Aparecido Antonio [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
Blood parasitosis is a frequent cause of anemia and myocarditis in dogs. Because anemia can trigger hypoxia or hemodynamic disturbances and myocarditis secondary to blood parasitosis can develop arrhythmias, electrocardiogram changes and increased levels of cardiac biomarkers, such as cardiac troponin I, are expected in dogs with blood parasitosis. Thus, this study aimed to investigate the electrocardiographic characteristics and the relationship to troponin I levels in anemic dogs with blood parasitosis. Twenty-eight dogs with blood parasitosis (seropositive for Ehrlichia canis/Babesia canis) and varying levels of anemia were evaluated. Dogs with very severe anemia (hematocrit below 13%) showed significant increases in heart rate when compared to dogs with severe, moderate or mild anemia. There was a predominance of respiratory sinus arrhythmia in dogs with mild, moderate and severe anemia and a high prevalence of sinus rhythm in dogs with very severe anemia, which showed a decrease in parasympathetic activity in this group. In all of the groups, electrocardiographic changes were detected showing compatibility with left and right atrial and left ventricular enlargement. Dogs with very severe anemia had a longer P wave duration. All groups of anemic dogs showed increased T-wave amplitude, suggestive of myocardial hypoxia. However, only the groups with moderate and severe anemia presented ST segment disturbances. Despite the lack of a correlation between the electrocardiographic changes suggestive of myocardial hypoxia and troponin I, there was a negative correlation (r = -0.95, p = 0.05) between hemoglobin levels and increased serum troponin. These data indicate that anemic dogs with blood parasitosis may have electrocardiographic changes suggestive of atrioventricular overload or hemodynamic disturbances, such as increased heart rate. Moreover, the negative correlation between hemoglobin and serum levels of troponin I may imply that dogs with severe and very severe anemia are at a higher risk for myocardial injury.
Keywords: Cardiac biomarker; electrocardiogram; hematocrit; myocardial hypoxia